(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This work considers the boundary value problem for a heterogeneous mixed-type partial differential equation with two degeneracy lines, obtains a representation of the solution, obtains an a priori estimate of the solution, and obtains theorems proving the uniqueness and conditional stability of the solution in the set of correctness.